2020
DOI: 10.1055/a-1179-1003
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting and Identifying Phyllanthus amarus Lignans with Antileishmanial and Antitrypanosomal Activity

Abstract: Ten lignans (1 – 10) were isolated from the hexane-ethyl acetate extract of Phyllanthus amarus leaves. Three of them, cubebin dimethyl ether (3), urinatetralin (4), and lintetralin (7) are described for the first time in this species, while phyllanthin (1), niranthin (2), 5-demethoxyniranthin (5), isolintetralin (6), hypophyllanthin (8), nirtetralin (9), and phyltetralin (10) have been already reported from P. amarus. Among the lignans tested against Trypanosoma cruzi intracellular amastigotes, 2 was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Some of the isolated lignans exhibited anti-trypanosomal activity comparable to benznidazole, a conventional treatment for Chagas disease. While previous studies reported anti-trypanosomal activity in plant-derived phenylpropanoids and lignans, compounds 5 and 8 demonstrated even greater potency compared to other reported lignans. Existing drugs for Chagas disease, such as benznidazole, nifurtimox, and fexinidazole, rely on nitro groups activated by trypanosome nitroreductase .…”
Section: Resultsmentioning
confidence: 63%
“…Some of the isolated lignans exhibited anti-trypanosomal activity comparable to benznidazole, a conventional treatment for Chagas disease. While previous studies reported anti-trypanosomal activity in plant-derived phenylpropanoids and lignans, compounds 5 and 8 demonstrated even greater potency compared to other reported lignans. Existing drugs for Chagas disease, such as benznidazole, nifurtimox, and fexinidazole, rely on nitro groups activated by trypanosome nitroreductase .…”
Section: Resultsmentioning
confidence: 63%
“…Chowdhury et al, have shown niranthin capability as a potent anti-leishmanial agent [20]. Recently Conrado et al 2020 have reaffirmed anti-leishmanial and anti-trypanosomal Activity activity of niranthin and other lignans from Niranthin [21]. Recently, our analysis for P.amarus and P. fraternus standardized extracts showed antxiolytic potential in mice models.…”
Section: Introductionmentioning
confidence: 67%
“…The present data showed that the selectivity index for (-)-5-demethoxygrandisin B was more prominent for Leishmania than for macrophages. Ten lignans isolated from the hexane-ethyl acetate extract of Phyllanthus amarus leaves showed that the CC 50 for all the samples was >100 µg/mL, thus revealing low cytotoxicity against macrophages and selectivity against the parasite [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that (-)-5-demethoxygrandisin B induced the depolarization of the mitochondrial membrane of the promastigote parasite, suggesting inhibition of the metabolic activity of parasites. L. amazonensis promastigotes treated with compounds like lignans change the mitochondrial membrane potential and lower ATP production [ 66 ]. Impairment of the membrane potential allows compounds to cross the mitochondrial membrane which may lead to a loss of the impermeability to intracellular electrolytes and consequently leads to inhibition of ATP production, resulting in parasite death [ 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%